2017
DOI: 10.1007/s10661-017-6117-x
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of trace elements and human health risk of submicron particulate matter (PM1) collected in the surroundings of coking plants

Abstract: Samples of PM1 were collected in the surroundings of coking plants located in southern Poland. Chemical fractionation provided information on the contents of trace elements As, Cd, Co, Cr, Hg, Mn, Ni, Pb, Sb and Se in all mobile (F1-F3) and not mobile (F4) fractions of PM1 in the vicinity of large sources of emissions related to energochemical processing of coal during the summer. The determined enrichment factors indicate the influence of anthropogenic sources on the concentration of the examined elements con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 61 publications
2
33
0
1
Order By: Relevance
“…Furthermore, pneumococcal bacteria which causes pneumonia has been shown to be more associated with BC than with PM 2.5 (Shears et al, 2020), suggesting that BC is a better indicator of harmful particulate substances from combustion sources than undifferentiated PM mass. Whilst PM 2.5 has been widely used in the literature as an indicator of indoor air pollution (Nicole AH Janssen et al, 2012;Zajusz-Zubek et al, 2017), new research is showing that it in itself contains PM 1 and BC in different proportions depending on the source (Nicole AH Janssen et al, 2012;Zajusz-Zubek et al, 2017). This nding highlights the importance to measure each pollutant and not depend on proxies or surrogate markers of the pollutants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, pneumococcal bacteria which causes pneumonia has been shown to be more associated with BC than with PM 2.5 (Shears et al, 2020), suggesting that BC is a better indicator of harmful particulate substances from combustion sources than undifferentiated PM mass. Whilst PM 2.5 has been widely used in the literature as an indicator of indoor air pollution (Nicole AH Janssen et al, 2012;Zajusz-Zubek et al, 2017), new research is showing that it in itself contains PM 1 and BC in different proportions depending on the source (Nicole AH Janssen et al, 2012;Zajusz-Zubek et al, 2017). This nding highlights the importance to measure each pollutant and not depend on proxies or surrogate markers of the pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…PM exists in different sizes usually denoted in µm, from PM 10 to PM 1 (Massey et al, 2012;Estimation, 2019). Accumulating evidence shows that PM 2.5 is dangerous to human health as it is able to penetrate nostril cilia and travel to the lungs where it can cause damage (Zajusz-Zubek et al, 2017). Particulate matter do not only differ in size but it also differs in composition depending on season and location (Massey et al, 2012;Carter et al, 2016;Estimation, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As compounds that are the most mobile in the natural environment and bioavailable to living organisms, i.e., those that are easily soluble in water will pose the greatest potential threat. A wide range of concentrations of PM-bound water-soluble As have been reported [9][10][11][12][13][14][15][16][17]. Generally, it was found that As in fine PM binds mainly in water-soluble compounds [10,11].…”
Section: Of 14mentioning
confidence: 99%